Management of Educational Financing Management in Elementary Madrasahs - Ara Hidayat; Aditya Nur Rohman; Diva Nur Wulandari; Lailatul Mahfiroh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the management of education financing management in Madrasah Ibtidaiyyah. Education financing is a crucial aspect in improving the quality of education, especially in Islamic education institutions such as Madrasah Ibtidaiyyah. In this study, a descriptive qualitative approach was used, and data were collected through interviews, observations and documentation studies. The results show that the management of financing in Madrasah Ibtidaiyyah includes planning, budgeting, implementation and evaluation. Good planning and transparency in budgeting greatly affect the effectiveness of the use of funds. In addition, community participation and cooperation with various parties, including government and private institutions, are important factors in supporting education financing. This study recommends increasing the managerial capacity of madrasah managers and developing better financial information systems to improve accountability and transparency in the management of education financing. Thus, it is expected that Madrasah Ibtidaiyyah can be more optimal in carrying out educational functions and achieving the expected goals.